Odpowiedź :
{2x + 4y = 5 / *(-2)
{4x - 8y = 4
{-4x -8y = -10
+ {4x -8y = 4
-------------------------
-16y= -6 / ÷ (-16)
y= ⅜
-4x -8 * ⅜ = -10
-4x - 3 = -10
-4x = -10 +3
-4x= -7 /÷ (-4)
x= 7/4
{x=7/4
{y=3/8
{4x - 8y = 4
{-4x -8y = -10
+ {4x -8y = 4
-------------------------
-16y= -6 / ÷ (-16)
y= ⅜
-4x -8 * ⅜ = -10
-4x - 3 = -10
-4x = -10 +3
-4x= -7 /÷ (-4)
x= 7/4
{x=7/4
{y=3/8
{2x + 4y = 5 /*2
{4x - 8y = 4
4×+8y=10
4x-8y=4
y się skrocą i zostaje 8x=14 czyli x=14/8 czyli 7/4 czyli 1 ¾
y=2*1¾+4y=5
{4x - 8y = 4
4×+8y=10
4x-8y=4
y się skrocą i zostaje 8x=14 czyli x=14/8 czyli 7/4 czyli 1 ¾
y=2*1¾+4y=5